Effect of treated silver nanoparticles to electrical conductivity improvement of electrically conductive adhesive (ECA) - Kornain Z. (2023)
Electrically conductive adhesive (ECA) is a popular alternative to replace lead solder interconnect material in most areas of electronic packaging. ECA mainly consists of an organic/polymeric binder matrix and metal filler. These composite materials provide both physical adhesion and electrical conductivity. Compared to the solder technology, ECA offers numerous advantages, such as environmental friendliness, lower processing temperature, fewer processing steps (reducing processing cost), and especially, the fine pitch capability attributed to the availability of small sized conductive fillers. Here, 70-nm sized silver particle filler (Ag) has been used to study the effect to electrical conductivity of ECA after surface treatment. Upon surface treatment of silver with silane-based coupling agent, the treated silver filled epoxy system demonstrated incredible improvement in electrical properties. The current conductivity (DC) for treated filler was 4.01 S/cm compared with untreated filler with 4.54E-03 S/cm for 5%w filler loading. Morphological studies using light microscopy micrographs have shown perceptible enhancement in filler dispersivity after treatment. 2008 IEEE.